Hispanic representation in diabetes cardiovascular outcomes trials. Issue 1 (4th May 2019) - Kelley, A. Taylor; Mizokami-Stout, Kara; O'Brien, Matthew J.; Bowen, Michael E.; Sussman, Jeremy
Abstract : Objective: To examine Hispanic/Latino representation in diabetes cardiovascular outcomes trials for novel antidiabetic drugs. Research design and methods: We compared Hispanic/Latino representation, age, gender and body mass index in diabetes cardiovascular outcomes trials published from January 2008 to October 2018 to Hispanic adults with diabetes in the National Health Examination and Nutrition Survey over the same time period. Results: Hispanics/Latinos comprised 18.5 % of trial subjects, which was similar to the proportion of US adults with diabetes who identify as Hispanic. Trial subjects were significantly younger, more likely to be female, and more obese than US Hispanics/Latinos. At least 10 different Latin American countries and territories were represented across the 10 trials. Conclusions: US Hispanics/Latinos differ from subjects in diabetes cardiovascular outcomes trials, which may limit generalizability of trial results.